Formulation of Natural Fortifiers from Readily Available Materials for Nutrient Enrichment of Organic Fertilizers - Taiwo B. Hammed; Godson R.E.E. Ana; Elizabeth O. Oloruntoba (Environment and Natural Resources Journal, 2019)
Studies have shown that organic fertilizer, a product of biodegradable organic matter, is not popular among Nigerian farmers because of its low quality. To alleviate this problem, this study was designed to explore the effect of nutrient-rich materials on quality of fertilizer made from market organic wastes. It adopted an experimental study design, comprising organic fertilizer preparation, fortification with natural fortifiers, farm plot experiments and laboratory analyses. The experiment was laid out in a randomized complete block design with factorial arrangement and three replications. The main plots comprised three crops - maize (cereal), soybean (legume) and yam (tuber) while five different fortified organic fertilizers at three rates of applications -2.0, 2.5, and 3.0 ton/ha and control (organic fertilizers without fortification) - formed subplots. Nutrient-rich materials sourced from animal, plant and rock changed the chemical composition of organic fertilizer made from market wastes and yielded better agronomic performances than the synthetic fertilizer. Hence, fortification of organic fertilizer with natural materials which are readily available and environmentally friendly should be promoted among the farmers.